A Proposed Diagnostic and Treatment Algorithm for the Management of Lumbar Discogenic Pain - Lorio MP; Beall DP; Myers TJ; Naidu RK; McRoberts WP; Davis TT; Gage EG; Calodney AK; Verrills P; De Palma MJ; Amirdelfan K; Block JE (Journal of Pain Research, 2025)
Morgan P Lorio,1 Douglas P Beall,2 Thomas J Myers,3 Ramana K Naidu,4 W Porter McRoberts,5 Timothy T Davis,6 Emmanuel G Gage,7 Aaron K Calodney,8 Paul Verrills,9 Michael J De Palma,10 Kasra Amirdelfan,11 Jon E Block12 1Orlando College of Osteopathic Medicine, Winter Garden, FL, USA; 2Comprehensive Specialty Care, Edmond, OK, USA; 3Paradigm Health System, Slidell, LA, USA; 4MarinHealth Spine Institute, Larkspur, CA, USA; 5Holy Cross Medical Group, Fort Lauderdale, FL, USA; 6Source Healthcare, Santa Monica, CA, USA; 7Centurion Spine & Pain Centers, Waycross, GA, USA; 8Precision Spine Care, Tyler, TX, USA; 9MetroPain Group, Clayton, VIC, Australia; 10Virginia iSpine Physicians, Richmond, VA, USA; 11Boomerang Healthcare, Inc., Walnut Creek, CA, USA; 12Private Practice, San Francisco, CA, USACorrespondence: Jon E Block, Private Practice, 2210 Jackson Street, Ste. 401, San Francisco, CA, 94115, USA, Tel +1 415-775-7947, Email jb@drjonblock.comBackground: There is renewed interest in the intervertebral disc as a target for treatments aimed at ameliorating lumbar discogenic pain by restoring and preserving the natural structure and function of this component of the vertebral motion segment.Methods: Using a modified Delphi methodology involving a panel of 11 experts, we developed a simple, understandable clinical algorithm to serve as a foundation for objective decision making regarding the diagnosis and treatment of lumbar discogenic pain throughout the entire continuum of care. A decision tree approach was utilized with “either/or” choices at each branch or node in the algorithm. Clinical activities in this algorithm were divided into examination procedures and corresponding treatment interventions. Corresponding treatment options were designated based on published degenerative disc disease (DDD)-specific clinical practice guidelines and/or meta-analyses.Results: This algorithm recommends a systematic rule set for discogenic pain diagnostic and treatment options. Initially, the presence of lumbar discogenic pain is confirmed via assessment of a series of clinical signs including axial midline back pain (≥ 4 of 10), pain with flexion, sitting intolerance, positive pain provocation with sustained hip flexion, and absence of motor/sensory/reflex changes. Radiographic severity of DDD is graded by modified Pfirrmann grade (1 to 8). Treatment options are stratified by DDD severity to include conservative management (grades 1 and 2), minimally-invasive intradiscal therapies (grades 3 to 7), and more invasive surgical procedures (grade 8). Recognizing that the management program for patients with lumbar discogenic pain can be highly personalized, the treatment options recommended by this algorithm should be considered general guidance.Conclusion: The proposed algorithm offers an easy-to-use clinical tool for identifying, evaluating and treating patients with lumbar discogenic pain. The successful implementation of this algorithm involves an important interplay between advanced practice providers, interventional pain physicians and spine surgeons.Keywords: discogenic pain, disc degeneration, intradiscal, minimally-invasive, algorithm